Hypoxia and Inflammation as a Consequence of β-Fibril Accumulation: A Perspective View for New Potential Therapeutic Targets. (26th June 2019) - Russo, Matteo A.; Tomino, Carlo; Vernucci, Enza; Limana, Federica; Sansone, Luigi; Frustaci, Andrea; Tafani, Marco
Abstract : Amyloidoses are heterogeneous diseases that result from the deposition of toxic insoluble β -sheet fibrillar protein aggregates in different tissues. The cascade of molecular events leading to amyloidoses and to the related clinical manifestations is not completely understood. Nevertheless, it is known that tissue damage associated to this disease involves alteration of tissue architecture, interaction with cell surface receptors, inflammation elicited by the amyloid protein deposition, oxidative stress, and apoptosis. However, another important aspect to consider is that systemic protein massive deposition not only subverts tissue architecture but also determines a progressive cellular hypertrophy and dilation of the extracellular space enlarging the volume of the organ. Such an alteration increases the distance between cells and vessels with a drop in pO2 that, in turn, causes both necrotic cell death and activation of the hypoxia transcription factor HIF-1 α . Herewith, we propose the hypothesis that both cell death and hypoxia represent two important events for the pathogenesis of damage and progression of amyloidoses. In fact, molecules released by necrotic cells activate inflammatory cells from one side while binding to HIF-1 α -dependent membrane receptors expressed on hypoxic parenchymal cells on the other side. This latter event generates a signaling cascade triggering NF κ B activation and chronic inflammation. Finally, we also suggest that this scenario, once proved and detailed, might suggest important targets for new therapeutic interventions.